Find the key experiment paradigm: Effect of numbers of object shape distractor on search time visual attention - Ahmad, Miqdad Daly; Sari, Navy Tri Indah; Nindita, Cantika Putri; Rukman, Putri Nurazizah; Kholista, Fairuzia Rana; Robaniya, Zida Inayatur (University of Muhammadiyah Malang, 2025)
The find the key paradigm is a digital psychology experiment paradigm which is a modification of the visual search paradigm. This paradigm is intended to focus on one of the pre-attentive visual attentions where the previous visual search used various pre-attentive visual attention features. While this paradigm focuses on finding out how the whole object can affect the search time of visual attention, for this reason the Find the Key paradigm was developed. This study used 116 individuals with a range of 18 to 26 years. Based on the results of the ANOVA analysis, it was found that there were significant differences from the four difficulty levels of the Find the Key paradigm, with search time increasing at more difficult levels. Therefore the number of types of distractor objects can affect visual attention.